2002
DOI: 10.1176/appi.ajp.159.6.1018
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Effects of Clozapine, Olanzapine, Risperidone, and Haloperidol in Patients With Chronic Schizophrenia or Schizoaffective Disorder

Abstract: Patients with a history of suboptimal response to conventional treatments may show cognitive benefits from newer antipsychotic drugs, and there may be differences between atypical antipsychotic drugs in their patterns of cognitive effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
299
1
5

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 487 publications
(326 citation statements)
references
References 29 publications
21
299
1
5
Order By: Relevance
“…Specifically, clozapine has demonstrated limited or no effects on executive function (Meltzer and McGurk, 1999;Hoff et al, 1996;Bellack et al, 2004). Risperidone has been shown either to be not effective (Bellack et al, 2004;Remillard et al, 2005;Lee et al, 2007) or slightly effective, as measured by Wisconsin Card Sorting Test (Meltzer and McGurk, 1999;Harvey et al, 2005), and olanzapine produces effects in the same range as risperidone (Meltzer and McGurk, 1999;Bilder et al, 2002;Keefe et al, 2007). In a small clinical trial, sertindole has shown superiority to haloperidol on executive function performance (Gallhofer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, clozapine has demonstrated limited or no effects on executive function (Meltzer and McGurk, 1999;Hoff et al, 1996;Bellack et al, 2004). Risperidone has been shown either to be not effective (Bellack et al, 2004;Remillard et al, 2005;Lee et al, 2007) or slightly effective, as measured by Wisconsin Card Sorting Test (Meltzer and McGurk, 1999;Harvey et al, 2005), and olanzapine produces effects in the same range as risperidone (Meltzer and McGurk, 1999;Bilder et al, 2002;Keefe et al, 2007). In a small clinical trial, sertindole has shown superiority to haloperidol on executive function performance (Gallhofer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This study has been criticized for high dropout rates, which were different between treatments (Weiss et al, 2002), and for a high average dosage of risperidone (Sharma, 2002). A subsequent 14-week study by Bilder et al (2002) confirmed that 10-40 mg olanzapine was superior to 10-30 mg haloperidol (particularly with regard to attention), but also found improvements in memory, which were most marked for 4-16 mg risperidone, implicating that different SGAs may differ in their patterns of cognitive effects. However, a large study of Harvey et al (2003), comparing the cognitive effects of 5-20 mg olanzapine or 2-6 mg/day risperidone over 8 weeks in 377 patients, found no differences between both treatments, while performance of all patients improved for several domains.…”
Section: Introductionmentioning
confidence: 92%
“…Among the advantages of these 'second-generation' antipsychotics (SGAs) (also referred to as 'atypical' or 'modern' antipsychotics) over 'first-generation' antipsychotics (FGAs) (also referred to as 'typical', 'traditional', or 'conventional' antipsychotics) are reduced extrapyramidal side effect profiles (Rosenheck et al, 1997;Simpson and Lindenmayer, 1997), reduced risk for tardive dyskinesia (Chouinard, 1995;Lieberman et al, 1994), greater effects on the negative and positive symptoms (Kane et al, 1988;Marder and Meibach, 1994;Beasley et al, 1996), and possibly beneficial effects on cognitive functioning (Purdon et al, 2000;Harvey et al, 2003;Bilder et al, 2002). SGAs have diverse receptor profiles, and the mechanism of action is still controversial (Seeman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16]57,58 Also, in these studies, different antipsychotics have been tested against each other. 57,58 In contrast, EPO has been able as an add-on treatment, on top of a stable antipsychotic medication regime, to specifically target cognition in a group of chronic schizophrenic patients with clearly defined, persistent cognitive decline. Even though the principal question Figure 4 Repeated-measures ANCOVA: effect of EPO versus placebo treatment on S100B serum levels in male chronic schizophrenic patients.…”
Section: H Ehrenreich Et Almentioning
confidence: 99%